Enhancing Decision-Making through Data Driven Approaches for Optimal Organisation Performance of Information Technology Companies in Sri Lanka - Dias, Mahathelge Shamira Chinthana (2025)
The study titled "Enhancing Decision-Making Through Data Driven Approaches for Optimal Organisation Performance of Information Technology Companies in Sri Lanka" investigates the critical role of data-driven approaches in improving organisational performance, emphasizing the need for a data-driven culture, data availability, and effective decision-making processes in today’s data-rich environment. Addressing the limited understanding of how these elements influence performance outcomes specifically within Sri Lanka's private sector IT context, the research evaluates the relationships among organisational performance, data-driven culture, data availability, and decision-making processes, with data quality as a moderating variable. Targeting approximately 120,000 IT executives across 300 companies, the study employs a quantitative approach grounded in deductive methodology, with data collected through structured surveys and analyzed using statistical techniques to test six hypotheses, all revealing strong correlations. The findings indicate that a robust data-driven culture, high data availability, and effective decision-making processes significantly enhance organisational performance, with data quality playing a crucial moderating role. In conclusion, the research underscores the importance of fostering a data-driven environment in private sector IT companies for optimal performance, recommending future studies to explore a broader range of variables, utilize advanced analytical methodologies, and integrate diverse theoretical perspectives to further enrich understanding of data-driven approaches in organisational contexts.